Acute green tea intake attenuates circulating microRNA expression induced by a high-fat, high-saturated meal in obese women: A randomized crossover study - Bastos, Rodrigo V.S. [UNESP]; Dorna, Mariana S. [UNESP]; Chiuso-Minicucci, Fernanda [UNESP]; Felix, Tainara F. [UNESP]; Fernandes, Ana A.H. [UNESP]; Azevedo, Paula S. [UNESP]; Franco, Estefânia T. [UNESP]; Polegato, Bertha F. [UNESP]; Rogero, Marcelo M.; Mota, Gustavo A.F. [UNESP]; Quintanilha, Bruna J.; Paiva, Sergio A.R. [UNESP]; et al. (Elsevier, 2023)
The objective of this study was to assess whether acute green tea (GT) supplementation attenuates inflammatory and oxidative stress biomarkers induced by high-fat, high-saturated (HFHS) meals in obese women, and to assess its ability to modulate circulating microRNA (miRNA) expression. This was a randomized, double-blind, crossover study. The study included obese women over 18 years old who had no comorbidities. In the first moment, patients were instructed to take 2 capsules of placebo or GT (738 mg) at 10:00 p.m. and to fast overnight. The next morning, a blood sample was collected, and an HFHS meal was offered to the patients. Another blood sample was collected 5 hours after the meal. In the second moment, patients who received placebo in the first moment now received the GT and vice-versa. Serum inflammatory and oxidative stress biomarkers were measured, and circulating levels of miRNA were evaluated. Fifteen women with mean age of 35.5±9.9 years were included in the final analysis. There was no difference regarding inflammatory and oxidative stress biomarkers. However, patients who consumed GT had lower circulating expression of 62 miRNAs compared with patients who did not consume GT. Predictive analysis of target genes showed 1,757 targets regulated by the 62 miRNAs. Notably, 5 miRNAs (miR-1297, miR-192-5p, miR-373-3p, miR-595 and miR-1266-5p) regulate genes associated with TGF-beta, CARM1, RSK, and BMP pathways. Our study showed that GT inhibited the expression of miRNAs induced by HFHS meal intake. These results shed light on the mechanisms involved in the beneficial effects of GT ingestion.
Keywords: Camellia sinensis; high-fat meal; inflammatory process; microRNA; oxidative stress